Influence Soft Skill, Hard Skill, and Internship Experience on the Job Readiness of Students of the Faculty of Economics and Business, State University of Jakarta - Nur Shabrina; Susi Indriani; Sri Widi Lestari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study seeks to investigate and evaluate the effects of soft skills, hard skills, and internship experience on the work readiness of students at the Faculty of Economics and Business, State University of Jakarta. A quantitative research approach was employed using primary data gathered through questionnaires. The study population comprised 732 students, from which 259 respondents were selected using a probability sampling method with a proportionate stratified random sampling technique. Data analysis was conducted using SPSS version 31, including descriptive statistics, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination (R²) analysis. The results indicate that: (1) soft skills have a positive and significant effect on work readiness; (2) hard skills positively and significantly affect work readiness; (3) internship experience positively and significantly affects work readiness; and (4) soft skills, hard skills, and internship experience simultaneously exert a positive and significant influence on the work readiness of students at the Faculty of Economics and Business, State University of Jakarta.